Contemporary Forms of Slovenian Love Charms Sodobne oblike slovenskih ljubezenskih čaranj - Babič, Saša (Studia mythologica Slavica, 2016)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Love was always one of the most desired emotions in history as it meant acceptance and tenderness. Therefore. people, mostly women (stereotypically (for Slovenian areas)), tried to gain love through magic, amulets and rituals, especially when marriages were mostly arranged by economic and social status. Therefore, it is surprising that there are almost no written sources for traditional love charms in Slovenian archives, though there are some descriptions of love magic rituals. In contrast, nowadays, we can find many internet sites with so-called love spells in the Slovenian language accompanied by some content explanations and also alleged historical descriptions. In this article Slovenian love spells which appear nowadays as a magic recipe for love on internet will be overviewed, their structure and content will be analysed, compared to traditional forms, and explanations within the cultural context will be given.